Biomechanical analysis of throw movement to second base in High School elite baseball catchers - Kim, S. Y.; Park, J. C.; Byun, K, S.; Baek, H. Y. (Korean Journal of Sport Biomechanics, 2020)
Objective: The purpose of this study was to provide quantitative and objective data of throwing movement in baseball catcher through biomechanical analysis. Method: Eight high school baseball catchers (age: 17.3±0.7 yrs, height: 175.3±4.5 cm, weight: 82.5±9.0 kg, Career: 7.4±2.1 yrs) participated and 3-dimentional motion capture system and electromyography (EMG) were used in this study. Results: The maximum center of mass position displacement was observed in forward direction. The linear velocity magnitude of the upper extremity segments were showed as "wrist>elbow>shoulder" which is indicative of kinematic chain. For kinetic EMG data, we also observed the greater muscle activation in the left brachioradial and erector spine muscles muscle that during throwing movement. Conclusion: We expect that biomechanical data from this study will provide important training implications to baseball coaches and trainers in order to effectively train their baseball catchers.